Albinism in Africa as a public health issue - Hong Esther S; Zeeb Hajo; Repacholi Michael H (BMC, 2006)
Abstract Background Oculocutaneous albinism (OCA) is a genetically inherited autosomal recessive condition and OCA2, tyrosine-positive albinism, is the most prevalent type found throughout Africa. Due to the lack of melanin, people with albinism are more susceptible to the harmful effects of ultraviolet radiation exposure. This population must deal with issues such as photophobia, decreased visual acuity, extreme sun sensitivity and skin cancer. People with albinism also face social discrimination as a result of their difference in appearance. The World Health Organization is currently investigating the issues concerning this vulnerable population. Methods Systematic electronic search of articles in PubMed concerning albinism in Africa. Furthermore, a World Health Organization (WHO) pilot survey of albinism was drafted in English, French and Portuguese, and distributed to African countries through WHO African Regional Offices (AFRO) in an attempt to gather further information on albinism. Results Epidemiologic data on albinism, such as prevalence, were available for South Africa, Zimbabwe, Tanzania and Nigeria. Prevalences as high as 1 in 1,000 were reported for selected populations in Zimbabwe and other specific ethnic groups in Southern Africa. An overall estimate of albinism prevalences ranges from 1/5,000 - 1/15,000. In addition, both the literature review and the survey underscored the medical and social issues facing people with albinism. Conclusion The estimated prevalence of albinism suggests the existence of tens of thousands of people living with albinism in Africa. This finding reiterates the need for increased awareness of and public health interventions for albinism in order to better address the medical, psychological and social needs of this vulnerable population.